Terrorism and Voting Behavior: Evidence from the United States - Leonardo Baccini; Abel Brodeur; Sean Nossek; Eran Shor (Global Labor Organization (GLO), 2021)
This paper examines the impact of terrorism on voting behavior in the United States. We rely on an exhaustive list of terror attacks over the period 1970-2016 and exploit the inherent randomness of the success or failure of terror attacks to identify the political impacts of terrorism. We first confirm that the success of terror attacks is plausibly random by showing that it is orthogonal to potential confounders. We then show that on average successful attacks have no effect on presidential and non-presidential elections. As a benchmark, we also rely on a more naïve identification strategy using all the counties not targeted by terrorists as a comparison group. We show that using this naïve identification strategy leads to strikingly different results overestimating the effect of terror attacks on voting behavior. Overall, our results indicate that terrorism has less of an in uence on voters than is usually thought.
Keywords: D72; D74; 330; terrorism; voting behavior